Undernutrition and Its Correlates among Children of 3–9 Years of Age Residing in Slum Areas of Bhubaneswar, India - Ansuman Panigrahi; Sai Chandan Das (The Scientific World Journal)
Undernutrition among children is a major public health concern worldwide, more prevalent in Asia and Africa. It manifests itself in various forms such as wasting or stunting or underweight and retards physical and mental development, increases susceptibility to infection, and reduces educational attainment and productivity. The present study was undertaken to assess the level of wasting, stunting, and underweight and determine its associates among slum children of 3–9 years of age, residing in Bhubaneswar city, India. After obtaining informed consent, a total of 249 children from 249 households were studied and their parents/guardians were interviewed to collect all relevant information. 23.3%, 57.4%, and 45.4% of children were found to have wasting, stunting, and underweight, respectively. Variables like birth order of child, period of initiation of breastfeeding and mother’s education were found to be strong predictors of wasting, whereas toilet facility in household and practice of drinking water storage were significantly associated with stunting among slum children as revealed in multiple regression analysis. Thus, a multipronged approach is needed such as giving priority to improve education for slum community especially for women, creating awareness regarding benefits of early initiation of breastfeeding, small family size, and proper storage of drinking water, and providing toilet facility in slum households which could improve the nutritional status of slum children.